Safety and structural integrity 2006 - Kim, Young-Jin, 1950- (Trans Tech Publications, 2007)
The primary objective of this collection of 42 peer-reviewed authoritative articles is to share with the reader the very latest information on cutting-edge technologies in the fields of safety and structural integrity. The topics addressed by this collection span a wide range of issues: including fracture and fatigue cracking, reliability evaluation, NDE, modeling and design. Particular attention is paid to emerging techniques for the treatment of complicated structures.
Keywords: Structural analysis (Engineering) -- Congresses.; Structural engineering -- Research -- Congresses.; Structural stability -- Congresses.; elektronické knihy; electronic books